Design of Surface-Active Artificial Enzyme Particles to Stabilize Pickering Emulsions for High-Performance Biphasic Biocatalysis - Chen, Zhaowei (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.